Penerapan Hiradc Pada Proyek Pembangunan Gedung Rumah Sakit BPJS Garut Dengan Metode JSA - Rega Maelani; Ida Farida (Jurnal Konstruksi, 2026)
The construction sector in Indonesia is growing rapidly due to its vital role in national development. However, this sector carries a high risk of workplace accidents, as it involves numerous workers, equipment, and construction materials. Data from 2019 to 2023 show that accident rates remain high, with key issues including project-related hazards, the level of risk associated with those hazards, and the need for effective risk mitigation efforts. To reduce accident rates, an Occupational Health and Safety Management System (OHSMS) based on OHSAS 18001:2007 has been implemented, which includes hazard identification, risk assessment, and risk control through the Job Safety Analysis (JSA) method.The study titled “Implementation of HIRADC in the Intan Husada Hospital Building Construction Project in Garut Using the JSA Method” aims to identify hazards, assess risks, and provide improvement recommendations to enhance workplace safety. This research makes a significant contribution by demonstrating that the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method based on JSA is more effective than conventional methods due to its systematic, in-depth, and practical approach in the context of construction projects.By identifying 78 potential hazards, the study found that before risk control measures were applied, there were 19 hazards (24 percent) classified as extreme risk, 42 (54 percent) as high risk, 16 (21 percent) as moderate risk, and 1 hazard (1 percent) as low risk. After implementing risk control measures, there were no longer any hazards classified as extreme or high risk; only 11 hazards (14 percent) remained at moderate risk, and 67 (86 percent) were categorized as low risk. This demonstrates the effectiveness of the HIRADC-JSA approach in significantly reducing risk levels.However, this study is limited to a single project at a specific location and time, so the results cannot yet be generalized. Further research is recommended across various types of projects with more variables—such as worker behavior, OHS training, and safety technologies—to produce more comprehensive findings.